The Relationship Between Parenting Style With The Biology Learning Outcome in SMAN 99 Jakarta Students - Farida, Luluk Nur; Irnidayanti, Yulia; Ernawati, E (Biosfer: Jurnal Pendidikan Biologi, 2015)
Learning outcome was influenced by interaction between child and parent, in this case parenting style. The aim of this research is to know the most parenting style and its correlation on Biology learning outcome in SMAN 99 Jakarta students. This research was based on parenting style theory from Macoby dan Martin’s. Macoby dan Martin’s assumed that parenting is a form of demandingness and supportiveness. There is four parenting style, authoritarian, authoritative, permissive indulgent and permissiveindefferent. Research methodology was descriptive method with correlational study. Sample was selected by simple random sampling technique comprised 125 students of clas X MIA SMAN 99 Jakarta. Data was taken by questionnaire. Data obtained in this research is processed with regression and correlation. Authoritative relationship with learning outcome in SMAN 99 Jakarta students has a positive and contribute for 79,2%.